Prevalence, pain intensity and symptoms associated with primary dysmenorrhea: a cross-sectional study - Jordana Barbosa-Silva; Mariana Arias Avila; Raissa Fernanda de Oliveira; Anny Caroline Dedicação; Amanda Garcia Godoy; Jessica Cordeiro Rodrigues; Patricia Driusso (BMC, 2024)
Abstract Background Primary dysmenorrhea (PD) is an etiological cyclic pelvic pain related to the menstrual period; it can negatively impact women's quality of life and productivity. The aim of the present study was to estimate the prevalence of PD and analyze associated symptoms in Brazilian women. Methods An online cross-sectional study was carried out in Brazil, with a structured questionnaire regarding dysmenorrhea and associated symptoms. PD intensity was measured with the Numerical Rating Scale for Pain and classified as mild (1-3), moderate (4-7) and severe (> 8). The association between qualitative variables was performed using Pearson's Chi-Square Test. The quantification of this association was measured using multinomial logistic regression models, with calculation of Odds Ratio and confidence interval. A significance level of 5% was considered. Results A total of 10,070 women were included. Most participants classified PD intensity as moderate (40.4%, 41.9% and 49.7%) and severe (21.2%, 24.8% and 28.4%) in the previous month, 3 months and 5 years, respectively. The most common symptoms associated with PD were irritability, abdominal distension sensation, anxiety and feeling more emotional. The increased of the risk (OR > 1.0) for moderate and severe PD-related pain intensity is related to age, nulliparity and presence PD since adolescence. Conclusion There is a high prevalence of PD among Brazilian women, and the most common symptoms reported were irritability, abdominal distension sensation, anxiety and feeling more emotional.